Price volatility in commodity markets with restricted participation - Andreas Knaut; Martin Paschmann (Institute of Energy Economics at the University of Cologne (EWI), 2017)
Analyzing commodity market dynamics, we observe that price volatility increases with reduced contract duration. In this paper, we derive a theoretical model depicting the price formation in two markets with altering product granularity. Supplemented by empirical evidence from German electricity markets for hourly and quarter-hourly products, we find that the high price volatility is triggered by restricted participation of suppliers in the market for quarter-hourly products as well as by sub-hourly variations of renewable supply and demand. Welfare implications reveal efficiency losses of EUR 96 million in 2015 that may be reduced if markets are coupled.
Keywords: C13; C51; D44; D47; L94; Q21; Q41; 330; commodity markets; price volatility; sequential market organization; short-term market dynamics; electricity market interaction; short-term price formation